Tour and Travel Services Company Website Design with Enhanced Awareness of Transportation Safety - Prasetyo, Iwan; Mirza, M. Navis; Kafidzin, Rohmad; Sekarningtyas, Hikmah; Faza, Iqbal (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Transportation safety is a critical aspect of the tour and travel industry. With increased focus on passenger safety and comfort, tour and travel companies must adopt information technology to enhance safety aspects. This article discusses the design and development of a tour and travel company website that is more safety-conscious, integrating important features such as NIK usage, passenger tracking, real-time notifications, and customer awareness education regarding safety. The design process employs the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) methodology. In summary, the new features added to the booking system have greatly improved user satisfaction and operational efficiency for the company. The safety-conscious website has positively impacted passenger safety and comfort. Technologies like NIK integration, real-time tracking, and automatic notifications have made the service more reliable and user-friendly. However, there's still a need for better education on safety requirements for drivers and vehicles, as many users admit to lacking understanding in this area. Continued efforts to educate users transparently can enhance trust and safety in transportation services.